2022
DOI: 10.3390/jcm11236941
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptional Profiling of Granulosa Cells from Polycystic Ovary Syndrome Patients: Comparative Analyses of Patients with or without History of Ovarian Hyperstimulation Syndrome Reveals Distinct Biomarkers and Pathways

Abstract: Ovarian hyperstimulation syndrome (OHSS) is often a complication of polycystic ovarian syndrome (PCOS), the most frequent disorder of the endocrine system, which affects women in their reproductive years. The etiology of OHSS is multifactorial, though the factors involved are not apparent. In an attempt to unveil the molecular basis of OHSS, we conducted transcriptome analysis of total RNA extracted from granulosa cells from PCOS patients with a history of OHSS (n = 6) and compared them to those with no histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Moreover previous studies have reported that insulin signaling, which includes INSR gene is essential for folliculogenesis, granulosa cell differentiation and ovulation and insulin resistance is one of the significant aberrations in polycystic ovarian syndrome (PCOS) [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover previous studies have reported that insulin signaling, which includes INSR gene is essential for folliculogenesis, granulosa cell differentiation and ovulation and insulin resistance is one of the significant aberrations in polycystic ovarian syndrome (PCOS) [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, high estradiol levels in the presence of human chorionic gonadotropin (hCG) increase the vascular endothelium permeability, leading to a massive shift of intravascular fluid into the third space. There are also evidences that during the pathogenesis of this iatrogenic complication, large amounts of angiotensin II, vascular endothelial growth factor (VEGF), interleukins (ILs), nitric oxide (NO), tumor necrosis factor-a (TNF-a), and other molecules are excessively produced, causing the overproduction of reactive oxygen species (ROS) which results in oxidant-antioxidant imbalance [ 8 ]. The vascular endothelium is then deteriorated by these imbalanced free radicals that cannot be antagonized by free radical scavengers; consequently, high vascular permeability occurs and finally results in the aggravation of OHSS [ 9 ].…”
Section: Introductionmentioning
confidence: 99%